Decentralisation at a Crossroads: How Fiscal and Administrative Autonomy Shape Regional Socio-Economic Efficiency - Beltrán-i-Cangrós, Albert; del-Canto-García, Senén; Gómez-Martínez, Raúl; Torres-Pruñonosa, José (International Regional Science Review, 2026)
A cross-sectional and longitudinal analysis of social and economic effects of regional administrative and fiscal decentralisation is carried out. Spain regions from 2008 to 2021 are analysed by means of Data Envelopment Analysis as well as bootstrapped Tobit regressions and panel data. The study contributes to ongoing debates in regional science by introducing a horizontal approach to decentralisation—comparing institutional variation across regions at the same administrative level—thus complementing the traditionally vertical analyses between levels of government. Results show that both administrative and fiscally decentralised regions have better socio-economic performance, except for 3 years when considering social efficiency of administrative decentralisation by means of cross-sectional analysis. This article contributes to the field of federalisation theory in the following three ways: (1) when recessions start, administrative decentralisation reduces social efficiency which justify centralisation to deal with crises; (2) the design of decentralisation is the key factor to be considered; (3) it is necessary to avoid the overlapping of regional public administration. The results offer theoretical support for second-generation fiscal federalism theories, which stress the importance of institutional design, governance quality and incentive alignment. For policy makers, the findings suggest that decentralisation per se is not sufficient: well-calibrated fiscal rules and institutional clarity are essential to enhance efficiency. Internationally, our evidence highlights lessons for federal and asymmetrically decentralised systems, particularly regarding the risk of inefficiencies stemming from overlapping competences.
Keywords: socio-economic efficiency; administrative decentralization; fiscal decentralization; public administration; regional governments; Spain